2021
DOI: 10.1088/1742-6596/1823/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

The Best Selection of PIP Scholarship: AHP-TOPSIS Vs Fuzzy AHP-TOPSIS

Abstract: The Smart Indonesia Program (PIP) is a program created by the government to address education problems in Indonesia. Selection of students who are entitled to PIP assistance is the main problem in this study, so this study aims to provide a comparison and evaluation of the selection of students who are entitled to PIP assistance. Previous research has been evaluated using the AHP-TOPSIS method and in this study comparing the method between AHP-TOPSIS vs Fuzzy AHP-TOPSIS, the purpose of this study is to obtain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Fuzzy TOPSIS method was introduced by Yoon and Hwang in 1980, It helps the researchers by comparing each alternative and rank the best alternative or the worst alternatives among all the alternative problems (Nadaban et al, 2016). On top of that, Wardana and Rianto (2021) indicated that TOPSIS method is simple and being selected to solve complex problems in various fields and also has been used by many researchers. As an example, Kusumawardani and Agintiara (2015) have used this method in their study to select the human resource manager in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Fuzzy TOPSIS method was introduced by Yoon and Hwang in 1980, It helps the researchers by comparing each alternative and rank the best alternative or the worst alternatives among all the alternative problems (Nadaban et al, 2016). On top of that, Wardana and Rianto (2021) indicated that TOPSIS method is simple and being selected to solve complex problems in various fields and also has been used by many researchers. As an example, Kusumawardani and Agintiara (2015) have used this method in their study to select the human resource manager in Indonesia.…”
Section: Introductionmentioning
confidence: 99%